A newly identified amino acid substitution T123I in the 14α-demethylase (Erg11p) of Candida albicans confers azole resistance. Issue 3 (25th February 2017) - Wu, YongQin; Gao, Ning; Li, Cui; Gao, Jing; Ying, ChunMei
Abstract: The increasing prevalence of azole resistance in Candida albicans poses a growing problem for clinical treatment. Amino acid substitution of the 14α-demethylase (Erg11p) encoded by the ERG11 gene is one of the most common mechanisms involved in azole resistance. Although amino acid substitutions of Erg11p have been observed in many clinical isolates, only a few amino acid substitutions have been confirmed to be related to azole resistance. In this study, by amplifying and sequencing the open reading frame of the ERG11 gene from 55 clinical isolates, we identified 27 fluconazole-resistant isolates that harbor a novel amino acid substitution, T123I, in Erg11p, in addition to the previously described homozygous substitution Y132H. We investigated both the contribution of this novel substitution T123I and its synergistic effect with substitution Y132H to azole resistance by heterogeneously expressing the C. albicans Erg11p with different substitution forms in Saccharomyces cerevisiae . Results showed that S. cerevisiae cells harboring the substitution T123I displayed higher (4-fold) minimum inhibitory concentration values to both fluconazole and voriconazole than the cells expressing the wild-type version of C. albicans Erg11p, but this was not true for itraconazolele. More importantly, a synergistic effect of substitutions T123I and Y132H was observed in an assay of voriconazole resistance. These results indicate that amino acid substitutions of Erg11p are prevalent among azole-resistant isolates and that the substitution T123I confers resistance to both fluconazole and voriconazole. Abstract : Amino acid substitutions of CaErg11p are prevalent and the substitution T123I confers resistance to azole, and has a synergistic effect on voriconazole resistance with the substitution Y132H.